A Study of LDL Status of Stroke Patient Admitted in Tertiary Care Hospital - Sarker, Nayan Ranjan; Rashid Un Nabi, Quazi Md; Saha, Swapan Kumar; Ghosh, Liton Chandra; Khan, Mohammad Ehasun Uddin (Sir Salimullah Medical College Journal, 2023)
Background: Stroke is the leading cause of morbidity globally and the second most frequent cause of mortality after ischemic heart disease. Previous findings regarding the relationship between lipids and stroke were debatable. Objective: To observe LDL status of stroke patients in tertiary care hospital. Method: This cross-sectional observational study was conducted in the Medicine Unit of Sir Salimullah Medical College Mitford Hospital, Dhaka from August 2011 to January 2012. A total of 104 patients of any sexes who were clinically present with features of stroke and then confirmed on CT scan were included. Patients were randomly enrolled according to the selection criteria. Data were collected using a structured questionnaire. Patients demographic profile, co-morbidities, history of TIA, and lipid profile were collected and recorded. Data were presented as frequency with percentage in case of categorical data and mean and standard deviation in case of numerical data. The Chi- Square test and unpaired t test was used to analyze categorical and numerical data respectively. A value of p <0.5 was considered statistically significant. Statistical software SPSS was used for data analysis. Result: The average age was 62.12±11.65 years. The majority of patients (61.5%) were men, while 38.5% were women. Out of 104 patients, 57.7% had high blood pressure, 33.7% had diabetes, 22.1% had IHD, and 26.0% had had a stroke or TIA in the past. 21.2% of the patients used smokeless tobacco, and about 41.3% smoked cigarettes. 73.1 percent of the patients had ischaemic strokes, and the remaining 26.9 percent had hemorrhagic strokes. It was found that dyslipidaemia was more frequently linked to ischaemic stroke than hemorrhagic stroke. Nearly 78.8% of stroke victims had high LDL levels, 44.2% had low HDL levels, 57.7% had high cholesterol, and 57.7% had high triglyceride levels. Patients who had ischaemic strokes were found to have higher levels of LDL than patients who had hemorrhagic strokes, but the difference was not statistically significant. Conclusion: Elevated LDL cholesterol was found higher in ischemic stroke patients than hemorrhagic stroke patients but there was no significant difference. Sir Salimullah Med Coll J 2023; 31: 53-59